2015
DOI: 10.1111/pme.12618
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Treatment Modalities for Neurosensory Disturbances of the Inferior Alveolar Nerve Following Retromolar Bone Harvesting for Bone Augmentation

Abstract: Our results justify SGB as a reasonable treatment modality for NSDs occurring after the harvesting of retromolar bone grafts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…This differs from Nogami and colleagues. who reported neurophysiological disturbances in 25% after different augmentation procedures such as bone block grafting, guided bone regeneration, or autogenous bone grafting combined with titanium mesh reconstruction …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This differs from Nogami and colleagues. who reported neurophysiological disturbances in 25% after different augmentation procedures such as bone block grafting, guided bone regeneration, or autogenous bone grafting combined with titanium mesh reconstruction …”
Section: Discussionmentioning
confidence: 99%
“…who reported neurophysiological disturbances in 25% after different augmentation procedures such as bone block grafting, guided bone regeneration, or autogenous bone grafting combined with titanium mesh reconstruction. 32 Therefore, a greater focus should be on investigating other causes To avoid sensory disturbances, different risk factors were tried to be excluded. Hence in CBR, when bone harvesting was necessary to compensate the 3-dimensional deficit, we chose the ramus donor site which is well-known for fewer complications and morbidity than the symphysis.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies investigating the effects of SGB on TNP had small sample sizes, short study periods, and included only a few surgery types 12,14 . Relative to such prior studies, the strengths of the current study are its larger sample size, longer study period, and use of additional surgery types.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent report, SGB was used for IAN paresthesia after retromolar bone harvesting for alveolar ridge augmentation before dental implant insertion. That study found that SGB accelerated recovery from postoperative neurosensory disturbances [ 13 ]. Although our study included only 4 patients treated with SGB, neurosensory symptoms ameliorated in those patients in whom SGB was initiated from 1 to 2 weeks after extraction, whereas both hypoesthesia and dysesthesia persisted in patients in whom SGB was initiated over 6 months postoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Nogami et al . [ 13 ], VB12 was administered in patients with neurosensory disturbances 1 week postoperatively, with a maximum medication period of 6 months; if there was no amelioration of symptoms, SGB was performed. Oral and maxillofacial surgeons should at least provide information about SGB if symptoms persist 2 weeks after extraction, especially in patients with dysesthesia.…”
Section: Discussionmentioning
confidence: 99%